Lesion Characteristics Difference and Cardiovascular Event in Drug-Coated Balloon Used for De Novo Patients - Masno, Adrian; Qonitah, Sarah; Akbar, Kiagus Muhammad Andri (Indonesian Health Journal, 2025)
Drug-Coated Balloon (DCB), a semi-compliant angioplasty balloon coated with an antiproliferative drug, is increasingly used for de novo lesions due to its “leave nothing behind” approach, which preserves vessel vasomotion and enables long-term remodeling. However, evidence for DCB in de novo lesions, especially small vessels, remains limited. This retrospective single-center cohort study analyzed 84 patients treated with DCB for de novo lesions at Mohammad Hoesin General Hospital, Indonesia (2023–2024). Lesions were grouped as Chronic Total Occlusion (CTO), Left Main (LM) disease, or bifurcation. Data from medical records and 6-month telecommunication follow-up identified major and non-major cardiovascular events. Bivariate analysis used SPSS Statistics 23 (p < 0.05 significant). CTO lesions linked significantly to cardiac arrest (20.4%, p = 0.005) but not recurrent heart attacks (9.3%, p = 0.102), bleeding (1.9%, p = 0.590), heart failure (7.4%, p = 0.164), revascularization (0%), or stroke (0%). LM disease and bifurcation lesions showed no significant associations with these events. Overall, 61.9% used biolimus agents. In conclusion, CTO lesions warrant careful selection and monitoring.